2014
DOI: 10.1016/j.jss.2013.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Milrinone-induced postconditioning reduces hepatic ischemia-reperfusion injury in rats: the roles of phosphatidylinositol 3-kinase and nitric oxide

Abstract: (237 words)Background: Ischemic postconditioning (PostC) protects the liver against ischemia-reperfusion (IR)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…There are also animal data to suggest a role of PDE3 inhibitors such as milrinone in promoting insulin secretion,15 which is a potential explanation for the hypoglycaemia observed in our patient. Animal studies have revealed a role for milrinone in ameliorating ischaemia-reperfusion injury in multiple organs, including the kidney16 and liver 4. Cycles of controlled ischaemia and reperfusion prior to an ischaemia-reperfusion event (preconditioning), or following an ischaemic event (postconditioning), are recognised methods to reduce organ injury secondary to ischaemia-reperfusion.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There are also animal data to suggest a role of PDE3 inhibitors such as milrinone in promoting insulin secretion,15 which is a potential explanation for the hypoglycaemia observed in our patient. Animal studies have revealed a role for milrinone in ameliorating ischaemia-reperfusion injury in multiple organs, including the kidney16 and liver 4. Cycles of controlled ischaemia and reperfusion prior to an ischaemia-reperfusion event (preconditioning), or following an ischaemic event (postconditioning), are recognised methods to reduce organ injury secondary to ischaemia-reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Cycles of controlled ischaemia and reperfusion prior to an ischaemia-reperfusion event (preconditioning), or following an ischaemic event (postconditioning), are recognised methods to reduce organ injury secondary to ischaemia-reperfusion. Beneficial effects of milrinone as an adjunct to preconditioning and postconditioning have both been described 4. Effects during preconditioning are mediated by activation of intracellular cyclic adenosine monophosphate (c-AMP) and c-AMP-dependent protein kinase A (PKA) 4 16.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations